Impact Of Play-Based Instruction And Jigsaw On Learning Motivation And Physical Fitness In Smk Tanjungpinang - Encik Nurissan Aprian; Umar Umar; Damrah Damrah; Nurul Ihsan (JETL (Journal of Education, Teaching and Learning), 2025)
This study investigates the influence of learning methods and student motivation on participation in Physical, Sport, and Health Education (PJOK) at SMK N 1 Tanjungpinang. The impetus for this research stems from observations indicating a low level of physical fitness among the student body, potentially attributable to a variety of factors, including pedagogical approaches and motivational levels. This quasi-experimental study involved 36 participants, selected based on pre- defined criteria. Physical fitness was assessed using the TKJI instrument, while motivation data were collected via a questionnaire. Data analysis was performed using a two-way analysis of variance (ANOVA) with a 2x2 factorial design. The results of the study and data analysis showed that: 1) There is a difference in physical fitness of students who are given the playing and jigsaw methods with a Sig value of 0.016 <0.05. 2) There is an interaction between learning methods and motivation on physical fitness, the Sig value between learning strategies and coordination skills is 0.000 < 0.05. 3) There is a difference in the level of physical fitness between students who are given the playing method and the jigsaw method at high learning motivation with a Qcount value of 14.54 > Qtable 3.85. 4) There is a difference in the level of physical fitness between students who are given the playing method and the jigsaw method at low learning motivation with a Qcount value of -2.65 < Qtable 3.85